2016
DOI: 10.1637/11456-062016-reg
|View full text |Cite
|
Sign up to set email alerts
|

Pathotyping and Phylogenetic Characterization of Newcastle Disease Viruses Isolated in Peru: Defining Two Novel Subgenotypes Within Genotype XII

Abstract: Infections of poultry with virulent strains of avian paramyxovirus 1 (APMV-1), also known as Newcastle disease viruses (NDVs), cause Newcastle disease (ND). This highly contagious disease affects poultry and many other species of birds worldwide. In countries where the disease is prevalent, constant monitoring and characterization of isolates causing outbreaks are necessary. In this study, we report the results of pathogenicity testing and phylogenetic analyses of seven NDVs isolated from several regions of Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…These indicated that the E115 strain was a virulent NDV strain, according to the OIE standard criteria. A phylogenetic tree based on the complete F gene sequence (1–1662 nt) showed that the E115 strain was assigned to subgenotype XIIb described by Chumbe et al () and was distinct from clusters of XIIa from Peru and XIId from Vietnam (Figures and ). The TMRCA for genotype XII NDVs in China was 2008.5 (95% highest posterior density [HPD] lower: 2000.9; 95% HPD higher: 2018.3).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…These indicated that the E115 strain was a virulent NDV strain, according to the OIE standard criteria. A phylogenetic tree based on the complete F gene sequence (1–1662 nt) showed that the E115 strain was assigned to subgenotype XIIb described by Chumbe et al () and was distinct from clusters of XIIa from Peru and XIId from Vietnam (Figures and ). The TMRCA for genotype XII NDVs in China was 2008.5 (95% highest posterior density [HPD] lower: 2000.9; 95% HPD higher: 2018.3).…”
Section: Resultsmentioning
confidence: 82%
“…Genotype XII NDVs were first reported in Peru, South America, and they have contributed to several ND outbreaks in chickens since 2004 (Chumbe et al, ; Diel, Susta, et al, ). Based on the ICPI and the sequence of the cleavage site in the F protein, these isolates were identified as virulent NDV strains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subgenotype XIIa strains have been isolated only in South America (Peru and Colombia) [1315], XIIb strains have been isolated only in the province of Guangdong in China [10,16] and XIId strains were recently reported in Vietnam [12]. XIIc is a potential subgenotype composed of strains isolated between 1986 and 2005, nevertheless only partial sequences of the F gene are available for these strains, therefore it cannot be consider as a proper subgenotype yet [13]. In Peru, XIIa is the only genotype isolated so far [13] and despite intensive vaccination campaigns, several outbreaks are reported every year [17], even in vaccinated flocks.…”
Section: Introductionmentioning
confidence: 99%
“…XIIc is a potential subgenotype composed of strains isolated between 1986 and 2005, nevertheless only partial sequences of the F gene are available for these strains, therefore it cannot be consider as a proper subgenotype yet [13]. In Peru, XIIa is the only genotype isolated so far [13] and despite intensive vaccination campaigns, several outbreaks are reported every year [17], even in vaccinated flocks. This can be explained by antigenic differences between vaccine and genotype XII circulating strains.…”
Section: Introductionmentioning
confidence: 99%